2020
DOI: 10.1111/ajd.13312
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of pigmented lesions managed by shave excision with no deep margin transection of melanomas

Abstract: Shave excision is a simple and cost-effective technique for the removal of suitable skin lesions. We performed a prospective study over six months, collecting data from pigmented lesions that were treated with shave excision by dermatologists. Only shave excisions with the intent to remove the lesion in toto were included. A total of 349 lesions were included in this study, 50 (14%) of these were melanomas and no melanoma diagnosed had deep margin involvement, while 13 (26%) had lateral margin involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“… 1 Studies have reported higher rates of sampling error and misdiagnosis with partial biopsies, accounting for over 50% of false-negative melanoma misdiagnoses. 2 To tackle this issue, Robinson et al 3 adopted a similar adhesive tape technique previously described for margin mapping large lesions guided by RCM 4 to navigate a punch biopsy performed in a case of recurrent lentigo maligna; however, this method has several limitations, such as its applicability with handheld RCM and punch biopsies only, restricting its clinical utility. Furthermore, this method relies on the constant repositioning of the tape, which may be time consuming, negating the benefits of rapid handheld RCM evaluation.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Studies have reported higher rates of sampling error and misdiagnosis with partial biopsies, accounting for over 50% of false-negative melanoma misdiagnoses. 2 To tackle this issue, Robinson et al 3 adopted a similar adhesive tape technique previously described for margin mapping large lesions guided by RCM 4 to navigate a punch biopsy performed in a case of recurrent lentigo maligna; however, this method has several limitations, such as its applicability with handheld RCM and punch biopsies only, restricting its clinical utility. Furthermore, this method relies on the constant repositioning of the tape, which may be time consuming, negating the benefits of rapid handheld RCM evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Partial shave biopsies may be appropriate for large tumours especially on the head and neck, distal limb or acral sites where large excisional biopsies may lead to unnecessary cosmetic or functional outcomes for some benign lesions. 3,[16][17][18][19] All partial shave biopsies of melanoma leave malignant melanocytes that will generally progress over time. The negative consequences of this growth may include disease progression, increased morbidity, decreased quality of life and shortened overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Although we cannot be certain that a correct diagnosis at the initial presentation would have prevented melanoma metastasis, the mean delay of more than 2 years before lesions were resampled to reach a correct diagnosis is concerning. Partial shave biopsies may be appropriate for large tumours especially on the head and neck, distal limb or acral sites where large excisional biopsies may lead to unnecessary cosmetic or functional outcomes for some benign lesions 3, 16–19 . All partial shave biopsies of melanoma leave malignant melanocytes that will generally progress over time.…”
Section: Discussionmentioning
confidence: 99%
“…Shave procedures pose minimal cost and morbidity for patients. 25 Shaves are a quick, same-day procedure removing any risk of non-compliance. We suspect shave procedures result in a lower biopsy threshold leading to a more favourable in situ to invasive ratio.…”
Section: Number Needed To Biopsymentioning
confidence: 99%